Development and Implementation of Diversity Programs in Large Collaborative Research Projects: An Example From Germany - Lorke, Mariya; Amelung, Rena; Kuchling, Peter; Paaßen, Benjamin; Pein-Hackelbusch, Miriam; Schloots, Franziska Margarete; Schulz, Klara; Nauerth, Annette (Diversity & Inclusion Research)
ABSTRACT In recent years, there has been an increasing awareness of the importance of incorporating diversity into research projects, focusing on both how they are conducted and their content. Funding organizations have started to require that research applicants pay attention to inclusion and diversity by considering gender dimensions and other diversity factors in their project plans and ensuring gender equality during execution. Based on an extensive literature research and expert discussions on how to develop and implement diversity strategies in large collaborative research projects, we argue that there is a lack of practical advice in existing literature. Drawing from our own experiences in conceptualizing and implementing a Diversity Program across four universities in Germany, we propose a framework for effectively integrating diversity into collaborative research initiatives across various academic fields.
Keywords: collaborative research projects; diversity strategy; gender equality